If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(b + -1c) = d (b * a + -1c * a) = d (ab + -1ac) = d Solving ab + -1ac = d Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Combine like terms: d + -1d = 0 ab + -1ac + -1d = 0 The solution to this equation could not be determined.
| x+108=100 | | 8+4d=36 | | 18+108=126 | | 8+4d=37 | | z=6*3.14xy | | 2-11x=122+x | | 20+3n=-4 | | -9x-4=23 | | 13-7x=58-28x | | 3(z-5)+6z-1= | | 2x+2x-5=19 | | 10x-130=1 | | 6k-(3k-6)= | | 8-3y=-13 | | 4x+5=41 | | 2+5x=26+5x | | (n-9)*9=27 | | 3(5x-1)=60 | | 2x+7y=24 | | y/5=25 | | (n-3)*2=16 | | log(x-13)=1 | | 4a-3a-2=2(3a-2) | | 7x+17=8x+8 | | 5X+26=X+50 | | n*6=100 | | -5x-35=5 | | y--28=y*32 | | 26-7p=15.50 | | 5x-8=5x-x | | 30n+40= | | -43-15= |